Pemanfaatan Limbah Kotoran Sapi Sebagai Bahan Utama Pembuatan Pupuk Organik untuk Mengurangi Penggunaan Pupuk Kimia di Desa Tebing Tinggi Pangkatan - Andrian Wiraguna; Fitra Syawal Harahap; Novilda Elizabeth Mustamu; Ika Ayu Putri Septyani (Universitas Mataram, 2022)
The population of cattle in the village of cliffs of high rank has enormous potential. This capacity is very good if used in the manufacture of organic fertilizer because in general cow dung waste has not been processed and utilized properly by the people of the village of cliffs of high rank. Agricultural activities of the high-ranking cliff village community which continuously result in the use of chemical fertilizers continue to increase, thus the use of organic fertilizers is an alternative in reducing community dependence in using chemical fertilizers in agriculture. The objectives of this community service are, 1) to carry out socialization and training to the community, 2) to understand more about the manufacturing procedure, the tools used, the materials used, how to use them on plants, and the benefits of manure. cows as an environmentally friendly organic fertilizer. The results of this dedication show that the manufacture of organic fertilizer requires the addition of materials, namely sawdust, rice water, coconut water, and brown sugar solution with the aim of increasing the nutrients of organic fertilizer. The application of organic fertilizers on agricultural land can reduce the manufacture of chemical fertilizers, but can improve the nutrients in the soil. Abundant cow dung is a great result for fixing nutrients in soils that are already highly dependent on chemical fertilizers. Therefore, the manufacture of organic fertilizers needs to be continuously disseminated to the community, especially farmers in rural areas who lack information and technology. This is possible through activities, knowledge and training. This service program is carried out using two methods, namely: face-to-face socialization, the practice of making organic fertilizers.